Experimental Characterization of Design Performance of Sand-Grained Asphalt Concrete for Worn Pavement - Bentata Aissa,; Kebaili, Nabil; Hachem Chaib, (International Journal of Sustainable Construction Engineering and Technology, 2024)
Most of the roads in Algeria are flexible pavements, the main component of which is asphalt concrete. Asphalt concrete aggregates made from crushed stone are now expensive and unavailable near roads, favoring the use of local materials such as dune sand, which is abundant in southern Algeria. The aim of this work is to study the rheological behavior of asphalt concrete, which is partially made of dune sand, as an alternative to crushed sand currently used. The effect of dune dosage on the rheological properties of concrete, in particular its compaction and rutting resistance, was determined using several formulations. To this end, various asphalt mixtures were tested on different dune sand grains using the Super pave rotary shear compaction (GSC) test by means of a rotary shear press to quantify their effect on compaction. These same asphalt mixtures were used to manufacture inserts for rutting tests. According to the results obtained, very acceptable values of resistance to rutting were achieved with 05 to 15% of dune sands compared to the reference concrete.